An error analysis of perfect tense among Islamic secondary school students in Terengganu - Ahmad Fahmi Ramli (Penerbit Universiti Kebangsaan Malaysia, 2020)
English language is a global language which has been spoken around the world for a long time. Some countries such as Malaysia considers English as a second language spoken along with Bahasa Melayu, the national language. However, not all Malaysians are able to speak English fluently with great accuracy due to the language errors produced, especially tense errors. Many have related this to perfect tense errors, considered to be the hardest to understand by many ESL learners. There are many categories of schools in Malaysia, in which all of these schools have to include English subject in the academic curriculum. In schools where English subject have received less attention, such as Islamic schools, the rate of students who can acquire advanced English is not very high. The main factor can be traced to lack of interest and practice. Despite this factor, students of English have to acquire perfect tenses in order to have complete mastery of English. This study aims to investigate perfect tense errors produced by secondary school students of Islamic schools in their written production. The error analysis method proposed by Dulay et al. (1982) was used to analyse the errors produced in the respondents’ essays in terms of Addition, Omission, Misinformation and also Misordering. This qualitative study recruited 15 sample short paragraphs produced by 15 form five students of Islamic secondary school in Terengganu. Subject matter experts were consulted to validate the analysed perfect tense errors. Data were analysed and presented in tabulated form. Results show that students frequently committed misinformation errors of perfect tense in their essays. This can be explained in terms of their confusion of perfect tenses as Bahasa Melayu is not a tense language but rather an aspect one. This study concluded that perfect tense errors are serious errors needing serious attention. It is recommended that students be raised of their awareness of perfect tense errors in their writing as a means of correcting and improving English proficiency.